Necrotizing Pneumonia Complicated by Early and Late Pneumatoceles - Suhail Al-Saleh; Hartmut Grasemann; Peter Cox (Canadian Respiratory Journal)
Community-acquired pneumonia generally has a benign course when treated, but can be complicated by pleural effusion, empyema, lung abscesses, necrotizing pneumonia or pneumatoceles. Pneumatoceles can cause cardiorespiratory compromise requiring urgent intervention. A child with a severe necrotizing pneumonia, as well as a large early pneumatocele complicating mechanical ventilation, is presented. While pneumonectomy resulted in transient improvement, the course was further complicated by multiple late occurring pneumatoceles that ultimately led to the patient’s death.